Analysis of classification of tourist multiplicator and its modern interpretation (Journal of Geography and Environmental Management, 2019)
The article considers the tourist multiplier’s various classifications based on the materials of domesticand foreign scientists and researchers. It was found that the tourism multiplier is the ratio of changesin one of the key economic indicators to changes of tourist expenses and is accompanied by a numberof other positive trends. Also, it has been determined that the indirect impact of tourism (the multiplicativeeffect of tourism) is much wider and deeper in its socio-economic nature and has a large numberof indirect effects, and its combined effect far exceeds the direct economic and social effect. After theresearch of the works of foreign and domestic authors not only in tourism, but also in other scientificfields, primarily economic theory, as well as for detailed and comprehensive consideration of the contentof the tourist multiplier, modern classification of the multiplier effect in tourism and tourist multiplierwas proposed, allowing deeper understanding of the essence and significance of the phenomenon understudy. Based on proposed classification, criteria were identified, such as the main types, degree of complexity,direction of action, nature of presentation, scale of manifestation, cause of occurrence, time ofdevelopment of tourist and recreational activities, forms of tourism, form of presentation and degree ofopenness of the tourist destination economy